The consequences of inaction towards antibiotic Misuse; XDR typhoid cases in Pakistan - Sajid, Zmareye (International Journal of Pathology, 2025)
The recent outbreak of extensively drug-resistant (XDR) typhoid cases in Pakistan has sent shockwaves throughout the medical community. The country is already grappling with a myriad of health challenges, and the emergence of XDR typhoid has added another layer of complexity to the existing healthcare crisis. Pakistan has had the worst rate of typhoid in South Asia, a problem that has only escalated since the emergence of XDR-typhoid.